Penerapan Arsitektur Smart Building pada Gedung Pemadam Kebakaran Modern di Kabupaten Bone - Fatimah, Andi Nurauliah; Nursyam, Nursyam; Rahim, Rahmiani (TIMPALAJA : Architecture Student Journals, 2024)
The fire department building is a building that has sophisticated technology. It takes technologies to help users in it. Users in this case are firefighters who must be required to have high mobility when receiving a report of a fire incident. Starting from the speed of receiving information, the speed of the officers in preparing the tools and equipment, going in and out of the building easily without being hampered by anything. Of course the building must have good technologies. As time goes by, which is now increasingly sophisticated and modern, the fire department building that is needed is a building that can provide sophisticated facilities, so that firefighters can carry out their duties to the fullest. Building design that has intelligent building capabilities where the management and control of electronic infrastructure operations in the building is carried out automatically. Therefore in this design the approach used is smart building. Smart building is a technology integration system with building installations that allows all devices in building facilities to be designed and programmed according to needs, wishes, and centralized automatic control or IBMS (Integrated Building Management system).